2005
DOI: 10.1111/j.1471-0307.2005.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and suckling on chymosin and pepsin activities in abomasums of goat kids

Abstract: The effects of age and suckling on the chymosin and pepsin activities in abomasums of goat kids were studied using column chromatography. The results showed that the chymosin activity in abomasums of suckling kids at 5 days of age was significantly greater than other age groups (P < 0.01); chymosin activity of random suckling kids decreased with increasing age (P < 0.01); chymosin activity of weaned kids gradually decreased from 10 to 20 days (P < 0.01), and then remained unchanged (P < 0.05); pepsin activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Andrén and Bjorck (1986) reported that with continuous suckling, the secretion of prochymosin could last at least 6 mo. Casein in the milk is the main factor causing the secretion of prochymosin; thus, the abomasa of calves fed a CN diet contain a higher level of chymosin and a stable level of pepsin (Zhang et al, 2005). In rennet paste from ARLb lambs, the beneficial influence of supplementing the milk substitute with Lb.…”
Section: Enzyme Composition Of Lamb Rennet Pastesmentioning
confidence: 99%
“…Andrén and Bjorck (1986) reported that with continuous suckling, the secretion of prochymosin could last at least 6 mo. Casein in the milk is the main factor causing the secretion of prochymosin; thus, the abomasa of calves fed a CN diet contain a higher level of chymosin and a stable level of pepsin (Zhang et al, 2005). In rennet paste from ARLb lambs, the beneficial influence of supplementing the milk substitute with Lb.…”
Section: Enzyme Composition Of Lamb Rennet Pastesmentioning
confidence: 99%
“…This produces oligopeptides and amino acids that are then taken up by enterocytes via specific transporters (Henning, 1985). By contrast, in the GI tract of zebrafish and suckling stage mammals, proteins are not fully digested in the lumen because of low protease activity (Henning, 1985;Robberecht et al, 1971;Rombout et al, 1985;Zhang et al, 2005). This allows antigens and maternal antibodies to be preserved and thus contribute to the development of innate and adaptive immune systems (Kulkarni and Newberry, 2019;Reinhardt, 1984).…”
Section: Introductionmentioning
confidence: 99%